2016
DOI: 10.1007/s11356-016-7530-3
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organochlorine pesticides and polychlorinated biphenyls in air of the North Sea region and air-sea exchange

Abstract: Organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) were studied to determine occurrence, levels and spatial distribution in the marine atmosphere and surface seawater during cruises in the German Bight and the wider North Sea in spring and summer 2009–2010. In general, the concentrations found in air are similar to, or below, the levels at coastal or near-coastal sites in Europe. Hexachlorobenzene and α-hexachlorocyclohexane (α-HCH) were close to phase equilibrium, whereas net atmospheric de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 61 publications
4
7
0
Order By: Relevance
“…In the offshore areas and the central North Sea, in contrast, were surface concentrations below a few pg L −1 . Our predictions were also consistent with results from [69] that showed concentrations of PCBs (sum of seven major congeners) typically ranging between less than 1 and 20 pg L −1 , with the higher levels occurring in the proximity of the German Bight and major river estuaries.…”
Section: Spatial-temporal Variability In Pcbsupporting
confidence: 89%
“…In the offshore areas and the central North Sea, in contrast, were surface concentrations below a few pg L −1 . Our predictions were also consistent with results from [69] that showed concentrations of PCBs (sum of seven major congeners) typically ranging between less than 1 and 20 pg L −1 , with the higher levels occurring in the proximity of the German Bight and major river estuaries.…”
Section: Spatial-temporal Variability In Pcbsupporting
confidence: 89%
“…The differences observed between basins result mainly from the global distillation of PCBs: low-chlorinated congeners volatilize in warm regions and are transported to colder ones, while highly chlorinated compounds remain closer to the sources of emission (Wania and Mackay 1996 ). This has been confirmed by Mai et al ( 2016 ) which reported that while higher-chlorinated PCBs have been found to be present in the air near the shoreline, more volatile congeners tend to be observed in the open waters far from shore. Significant roles are also played by the concentration of point sources of PCB emission along the shoreline of the water body.…”
Section: Resultssupporting
confidence: 65%
“…Additionally, the polar regions, where agricultural activities are far away, may also receive significant quantities of CUPs released by sea ice melt in summer (Ma et al, 2011). Similar to the behaviors through atmospheric transport, distributions of CUPs in seawater are dynamic and changeable during transportation by ocean currents (Hargrave et al, 1997), with concentrations decreasing over time and distance (Mai et al, 2016) in accordance with microbial activities in water and CUPs' environmental persistence (as characterized by half-lives).…”
Section: Introductionmentioning
confidence: 99%